Growth kinetics, metabolomics changes, and antioxidant activity of probiotics in fermented highland barley-based yogurt. (1st January 2023) - Li, Kailing; Duan, Zhi; Zhang, Jingyan; Cui, Hongchang
Abstract: Fermenting yogurt with plant-based ingredients for nutritional and health benefits is an emerging trend. The growth kinetics, metabolomics changes, and antioxidant activity of probiotics in fermented highland barley-based yogurt were investigated in this study. Highland barley (HB) ( Hordeum vulgare, Poaceae) enzyme hydrolyte was mixed with soy protein concentrate as ingredients for preparation of HB-based yogurt fermented by Lactobacillus bulgaricus VHProbi R03 and Streptococcus thermophilus VHProbi R08. After 4 h of fermentation, both strains grew to the stationary phase with the viable counts of 1.9 × 10 8 CFU/mL for each strain. The viable bacterial count in HB-based yogurt was approximately 9.3 × 10 7 CFU/mL after 21 days of storage at 4 °C. Compared with the control yogurt made using white sugar (as a substitute for HB enzyme hydrolyte) and soy protein concentrate, HB-based yogurt had higher concentrations of cyclic adenosine monophosphate, glycerophosphocholine, hypoxanthine and arginyl-proline, total phenolic compounds, and flavonoids, greater antioxidant activity, and higher sensory scores. In conclusion, HB-based yogurt is a potential novel food product that provides a good source of probiotics and antioxidants. Highlights: Highland barley-based yogurt has higher antioxidant activity. Total phenolic and flavonoid contents of Highland barley-based yogurt significantly higher after fermented. 27 top metabolites with significant changes in fermented Highland barley-based yogurt. The properties of Highland barley-based yogurt were stable during storage.